A Systematic Approach to Critical Electrical Fault Mitigation Strategies in an Electric Vertical Take-Off and Landing (EVTOL) Electrical Propulsion Unit - Ramoul, John (My University, 2022)
The electric vertical take-off and landing (EVTOL) platform is opening a new market segment that is disrupting the commercial and military aircraft industry. This particular vehicle platform is filling the gap between road vehicles and aircrafts. The main idea is to avoid the gridlock in major metropolitan cities where a journey that should take 30 minutes now takes more than one hour. Key enablers such as the newly developed infrastructures known as Vertiports and the move of electrification of aircrafts have driven this new market segment with fast time to market. To enable the deployment of these EVTOLs in the commercial world, their fault behavior needs to be known as faults will happen, a fault mitigation strategy must be developed to ensure that when the fault happens, the EVTOL and its passengers along with its surrounding are protected from catastrophic failures. To give a brief context on what these EVTOL platforms are, potential and developed EVTOLs in the market currently are introduced. The categorization of these platforms is done within four types of categories being Helicopters, Multi-Rotor, Lift & Thrust and Tilt-X. Their general advantages and disadvantages are discussed and the categories are rated in terms of which platform could be the most viable option to be in service by 2024. Their main electrical distribution system is introduced with their critical components and how they can fail. Each critical component such as the battery, electrical propulsion unit (EPU), protection devices, power distribution units and auxiliary electrical loads are discussed in details. The thesis discusses one of the main safety aspects of an EVTOL, which is protection of a propulsion unit. The critical electrical faults in the EPU are introduced along with their behavior on the EVTOL electrical distribution system (EDS). Open circuit faults and short circuit faults from the inverter and its power devices to the electric motor are analyzed. Furthermore, the sensor failures such as the rotor position sensor and the current and voltage sensors are discussed. The controller stage failures are discussed as well as it becomes a critical component that can fail in many ways. Once the electrical faults are discussed, a fault mitigation strategy (FMS) is introduced for each fault ranging from a simple inverter disabling strategy, to a sensorless control law for the loss of position sensor. A protection device known as the solid state power controller (SSPC) is inserted at the input of the EPU and its design is discussed for a 270VDC/180A modular architecture. This SSPC becomes the redundant and final protection stage of the EPU to ensure if the developed FMS fail to protect the EPU, the SSPC can isolate the EPU from the rest of the EVTOL EDS. The main contribution of the thesis is the systematic approach to fault analysis and mitigation/protection strategies that were not addressed in literature so far for this type of platform. The use of a single FMS for multiple faults is introduced where the aim is to reduce the efforts for verification and validation (V&V) of the corresponding software and firmware. Finally, the practical implementation challenges of the SSPC are discussed and shown in experimental lab setups.
Keywords: EVTOL; Electrical propulsion unit; Fault Protection; Electrical fault; Solid State Power Controller